The Astrojildo Pereira's last days: the separation of his archive and the consequences for the construction of historiography on the Brazil labor movement - Maldonado, Luccas Eduardo (Revista de História, 2023)
This text aims to historically map the destinies of Astrojildo Pereira’s personal archive in the second half of the 20th century and the beginning of the 21st. This man accumulated a large number of documents and books linked to his political activism and literary activity. The material did not have a simple destination. It was not referred to a safekeeping institution. It was separated into several parts due to state interference and family economic difficulties. The collection would be made available for research in four parts at the three public higher education institutions in the state of São Paulo decades later.